Landscape influences genetic diversity but does not limit gene flow in a Neotropical pollinator - de Matos Barbosa, Marcela; Jaffé, Rodolfo; Carvalho, Carolina S.; Lanes, Éder C. M.; Alves-Pereira, Alessandro; Zucchi, Maria I.; Corrêa, Alberto S.; Ribeiro, Milton C. [UNESP]; Imperatriz-Fonseca, Vera L.; Alves, Denise A. (Springer Nature, 2022)
Tropical landscapes are rapidly changing due to deforestation and agricultural expansion, entailing the loss and fragmentation of natural habitats. Understanding how these changes affect the genetic diversity and gene flow in key native pollinators is of great importance to assure their survival and provision of pollination services. In this context, we studied how landscape features influence genetic diversity and gene flow in one of the most widespread species of stingless bees in the Neotropical region, Tetragonisca angustula. We evaluated bees from 46 nests sampled across forested, agricultural and urban landscapes within the Atlantic Forest, genotyped at 745 single-nucleotide polymorphisms (SNPs). We found that forest cover negatively influenced the heterozygosity at a 500-m scale, although inbreeding and gene flow were not influenced by landscape features. Gene flow was explained mainly by geographic distance, indicating that T. angustula can disperse across heterogeneous and human-altered landscapes.
Keywords: landscape genetics; rainforest; SNPs; stingless bees; Tetragonisca angustula